An Integrated Strategy to Identify and Quantify the Quality Markers of Xinkeshu Tablets Based on Spectrum-Effect Relationship, Network Pharmacology, Plasma Pharmacochemistry, and Pharmacodynamics of Zebrafish - Wei, Yongheng; Nie, Lei; Gao, Lele; Zhong, Liang; Sun, Zhongyu; Yang, Xiangchun; Yue, Jianan; Zeng, Yingzi; Li, Lian; Sun, Jing; Zang, Hengchang (Frontiers in Pharmacology, 2022)
Xinkeshu Tablets (XKST), a traditional Chinese Patent Medicine (CPM), has served in clinical treatment of cardiovascular diseases (CVDs) for decades. However, its pharmacodyamic material basis was still unclear, and the holistic quality control has not been well established due to lack of systematic research on the quality markers. In this experiment, the heart rate recovery rate of zebrafish larva, was used to evaluate a traditional efficacy of XKST, antiarrhythmic effects. The HPLC fingerprints of sixteen batches of XKST samples were obtained, and antiarrhythmic components of XKST were identified by establishing the fingerprinting-efficacy relationship between HPLC fingerprints and heart rate recovery rate of zebrafish larva with orthogonal signal correction and partial least squares regression (OSC-PLSR) analysis. Anti-cardiovascular disease components of XKST were identified by mapping of targets related to CVDs in network pharmacology. Compounds of XKST absorbed and exposed in vivo were identified by ultra-high performance liquid chromatography Q-Exactive high resolution mass spectrometry (UHPLC-Q-Exactive HRMS). Based on the above studies, combined with five principles for identifying quality markers and verified by a zebrafish arrhythmia model, danshensu, salvianolic acid A, salvianolic acid B, daidzein and puerarin were identified as quality markers of XKST. Sixteen batches of XKST samples were further quantified with the method established in this study. Our study laid the foundation for quality control of XKST. The integrated strategy used in the study of XKST could be applied for the identification and quantification of quality markers of other CPM as well.